2018
DOI: 10.1002/cphc.201701240
|View full text |Cite
|
Sign up to set email alerts
|

Trapping One Electron between Three Beryllium Atoms: Very Strong One‐Electron Three‐Center Bonds

Abstract: The ability of a set of beryllium-substituted cyclohexane derivatives to trap electrons was determined by evaluating their electron affinities at the G4(MP2) level of theory. The nature of bonding and the effect of the different substituents attached to beryllium were studied by different computational methods (quantum theory of atoms in molecules, electron localization function, natural bond orbital, and analysis of the spin density), revealing the existence of a one-electron/Be cyclic bonding in trisubstitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…The most important conclusion we can extract from our previous discussion, and in conjunction with previous studies in the literature, , is that derivatives in which two or more BeX groups are close to each other lead to rather stable anionic systems, due to the ability of such compounds to form one-electron multicenter bonds. In the particular case of the C 4 H 4 (BeX) 4 (X = H, Cl) derivatives studied in this case, the anionic global minima exhibit, as we discussed above, one-electron four-center Be bonds.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The most important conclusion we can extract from our previous discussion, and in conjunction with previous studies in the literature, , is that derivatives in which two or more BeX groups are close to each other lead to rather stable anionic systems, due to the ability of such compounds to form one-electron multicenter bonds. In the particular case of the C 4 H 4 (BeX) 4 (X = H, Cl) derivatives studied in this case, the anionic global minima exhibit, as we discussed above, one-electron four-center Be bonds.…”
Section: Discussionsupporting
confidence: 67%
“…The same intrinsic property, a high Lewis intrinsic acidity, is behind the high electron affinity predicted for compounds that, as 1,8-diBeX-naphthalene derivatives, present two Be atoms physically close, and therefore in optimal conditions to form one-electron two-center bonds. , A similar bonding arrangement, through the formation of one-electron three-center bonds, is responsible for the high electron affinities (134 kJ mol –1 ) predicted for tri-BeH-substituted cyclohexane derivatives …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…These bonds were found to modulate the strength of other non‐covalent interactions, such as hydrogen bonds, 48 halogen bonds, 49 and other weak intermolecular interactions 50 . It was also found that beryllium bonds can spontaneously produce radicals, 51 or very strong one‐electron three‐center bonds 52 . Many other characteristics can be found in a recent compilation on this bond 53 .…”
Section: Introductionmentioning
confidence: 88%
“… 50 It was also found that beryllium bonds can spontaneously produce radicals, 51 or very strong one‐electron three‐center bonds. 52 Many other characteristics can be found in a recent compilation on this bond. 53 Some attention has also been paid to Be clusters, where already the simplest, Be 2 , was the subject of a long‐standing controversy as to its stability since early CI calculations predicted its ground state of being repulsive, 54 whereas more recent studies indicate that the bonding in Be 2 is essentially due to non‐dynamical correlation effects.…”
Section: Introductionmentioning
confidence: 96%